The strength development and chloride permeability of concrete containing natural pozzolan and limestone powder at different curing temperatures - Pham, Van Toan (Journal of Transportation Science and Technology, 2025)
This study investigated the strength development and chloride permeability of concretes by considering not only the effects of limestone powder and natural pozzolan but also the initial curing temperature. The study examined the mechanical and chemical changes in the concretes cured at different initial curing temperatures, including 20oC and 60oC. The results revealed that the compressive strength of concrete containing natural pozzolan was higher than that of the concrete without natural pozzolan after 28-day curing at 20oC, namely normal temperature. 60oC, namely high curing temperature, was responsible for increases in the compressive strength of concretes at early ages and reductions at later ages in comparison with that of concretes cured at normal curing temperature. The effect of limestone powder on concrete strength was insignificant at both curing temperatures. Furthermore, using natural pozzolan and limestone powder as a fine aggregate replacement improved the chloride impermeability of concretes.
Keywords: Concrete; Natural pozzolan; Limestone powder; Compressive strength; Chloride permeability; Curing temperature